Vitrocerâmicas transparentes não-estequiométricas de silicato de lítio reforçadas por troca iônica - Santana, Geovana Lira (2024)
Glass-ceramics generally exhibit superior mechanical, electrical, and thermal properties compared to their parent glasses. However, achieving these properties often requires crystal growth, which increases light scattering and reduces transmittance. To overcome this drawback, ion-exchange processing can be employed to enhance the mechanical strength of these materials while maintaining transparency in the visible range. This process, widely applied in glass strengthening, consists of replacing alkali ions on the glass surface with larger ones from a molten salt bath. The size mismatch generates a compressive stress layer that reinforces the glass-ceramic. Nevertheless, the mechanisms of chemical strengthening in glass-ceramics remain not fully understood due to their complex microstructure. In this context, this thesis developed transparent lithium silicate glass-ceramics reinforced through ion exchange. The study, organized into chapters, first analyzed the influence of nucleating agents on obtaining transparent glass-ceramics with a high crystallized fraction (~80%) and high transmittance (80% at 550 nm) within reduced crystallization times. Additionally, the effect of microstructure (crystallized fraction) on mechanical strength and on the depth of layer (Li⁺ ↔ Na⁺) was investigated. The results revealed a stronger tendency for chemical strengthening in glass-ceramics with lower crystallized fraction (~50%), which reached flexural strength values of 767 and 670 MPa for the GN8 and GN9 compositions, respectively. Furthermore, experimental evidence indicated that the decrystallization phenomenon occurred preferentially in these samples, mainly affecting the lithium metasilicate crystalline phase. Overall, the results highlight the potential for producing transparent lithium silicate glass-ceramics within reduced processing times and demonstrate the effectiveness of the ion-exchange process in strengthening these materials.